Genetic screen in a large series of patients with primary progressive aphasia. Issue 4 (29th December 2018) - Ramos, Eliana Marisa; Dokuru, Deepika Reddy; Van Berlo, Victoria; Wojta, Kevin; Wang, Qing; Huang, Alden Y.; Miller, Zachary A.; Karydas, Anna M.; Bigio, Eileen H.; Rogalski, Emily; Weintraub, Sandra; Rader, Benjamin; et al.
Abstract: Introduction: Primary progressive aphasia (PPA) is a neurological syndrome, associated with both frontotemporal dementia and Alzheimer's disease, in which progressive language impairment emerges as the most salient clinical feature during the initial stages of disease. Methods: We screened the main genes associated with Alzheimer's disease and frontotemporal dementia for pathogenic and risk variants in a cohort of 403 PPA cases. Results: In this case series study, 14 (3.5%) cases carried (likely) pathogenic variants: four C9orf72 expansions, nine GRN, and one TARDBP mutation. Rare risk variants, TREM2 R47H and MAPT A152T, were associated with a three‐ to seven‐fold increase in risk for PPA. Discussion: Our results show that while pathogenic variants within the most common dementia genes were rarely associated with PPA, these were found almost exclusively in GRN and C9orf72, suggesting that PPA is more TDP43‐ than tau‐related in our series. This is consistent with the finding that PPA frequency in dominantly inherited dementias is the highest in kindreds with GRN variants.